Radiative sky cooling of silicon solar cells: investigation of photonic pathways through coupled optical-electrical-thermal modelling - Dumoulin, Jeremy; Drouard, Emmanuel; Amara, Mohamed (2021 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2021)
Photovoltaic (PV) solar cells are designed to efficiently absorb solar photons but convert only a limited proportion of them into electricity. The remaining energy is converted into heat, which in turn, heats solar modules up to 50-60 °C under real operating conditions [1] , which is detrimental to their power conversion efficiency and lifetime. In recent years, there has been a growing interest in the so-called radiative sky cooling (RSC) strategy. This approach consists in optimizing the thermal radiation of cells or modules - with the help of photonic structures - by taking advantage of the atmospheric transparency in the 8-13 μm range [2] , [3] . Although some preliminary studies on the subject predict cooling of more than 13°C on silicon wafers [4] , they remain insufficient to fully assess the potential of this technique for various cell and module technologies.